2014
DOI: 10.15388/informatica.2014.22
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Human Emotions as Reactions to a Dynamical Virtual 3D Face

Abstract: Abstract. This paper introduces a comparison of one linear and two nonlinear one-step-ahead predictive models that were used to describe the relationship between human emotional signals (excitement, frustration, and engagement/boredom) and virtual dynamic stimulus (virtual 3D face with changing distance-between-eyes). An input-output model building method is proposed that allows building a stable model with the smallest output prediction error. Validation was performed using the recorded signals of four volunt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…is the Euclidean norm sign, γ 0 is a small and positive constant. When n 2 (stability domain for the model (2) is defined by linear inequations) factor γ calculation was given (Kaminskas et al, 2014) and when n 3 (stability domain is defined by linear and quadratic inequations) factor γ calculation was given (Kaminskas and Vidugirienė, 2016). Estimates of the model orders (m,n) are defined from the following conditions (Kaminskas and Vidugirienė, 2016):…”
Section: Parameter Identification Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…is the Euclidean norm sign, γ 0 is a small and positive constant. When n 2 (stability domain for the model (2) is defined by linear inequations) factor γ calculation was given (Kaminskas et al, 2014) and when n 3 (stability domain is defined by linear and quadratic inequations) factor γ calculation was given (Kaminskas and Vidugirienė, 2016). Estimates of the model orders (m,n) are defined from the following conditions (Kaminskas and Vidugirienė, 2016):…”
Section: Parameter Identification Methodsmentioning
confidence: 99%
“…Dependency between human excitement signal as a response to a virtual 3D face feature (distance-between-eyes) changes is described by linear input-output structure model (Kaminskas et al, 2014)…”
Section: Input-output Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Three types of 3D face features (distance-between-eyes, nose width and chin width) were used for human reaction elicitation and four EEG-based response signals (excitement, frustration, engagement/boredom and meditation) were observed and analyzed in previous research [46]. Analysis of the results has shown that all three types of the 3D face feature have triggered similar human reaction signals, accordingly distance-between-eyes was selected and used as a dynamic 3D face feature in further research [24], [26], [28]. From observed four EEG-based response signals, excitement is the most variable signal.…”
Section: Control Plantmentioning
confidence: 99%
“…Linear and nonlinear predictive models of the input-output structure were proposed and investigated for exploring dependencies of the EEG-based emotion signals as a human response to a dynamic virtual 3D face features when a virtual 3D face is observed without a virtual reality headset [24], [26], [46]. The technique of dynamic systems identification which ensures stability of the models is applied to build these models [14].…”
Section: Introductionmentioning
confidence: 99%